2015
DOI: 10.3892/ol.2015.3592
|View full text |Cite
|
Sign up to set email alerts
|

Primary extragonadal germ cell tumor: A case report on prostate seminoma

Abstract: Abstract. Primary extragonadal germ cell tumors are rare, and 60% of such cases are seminomas. While the tumors can occur in the mediastinum, thymus, retroperitoneal organs and pineal gland, seminoma originating in the prostate tissue is extremely rare. The present study reports the case of a 54-year-old male with prostate seminoma. The patient was followed up at the First Affiliated Hospital of Dalian Medical University (Dalian, Liaoning, China) from 2001 onwards. The patient received chemotherapy with cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…[ 2 ] Primary extragonadal germ cell tumors of the prostate are very rare, with fewer than 20 cases described in the literature. [ 6 , 7 ] Hashimoto et al reported a primary seminoma of the prostate in a 54 years old male, whose main complaint was difficulty with urination. They first suspected sarcoma of the prostate and were diagnosed with seminomas by needle biopsies of the prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Primary extragonadal germ cell tumors of the prostate are very rare, with fewer than 20 cases described in the literature. [ 6 , 7 ] Hashimoto et al reported a primary seminoma of the prostate in a 54 years old male, whose main complaint was difficulty with urination. They first suspected sarcoma of the prostate and were diagnosed with seminomas by needle biopsies of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with KS have substantially decreased androgen levels, the risk of prostate cancer is significantly decreased [2] . Primary extragonadal germ cell tumors of the prostate are very rare, with fewer than 20 cases described in the literature [6,7] . Hashimoto et al reported a primary seminoma of the prostate in a 54 years old male, whose main complaint was difficulty with urination.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our case, five of the six cases with outcome data noted invasion of adjacent structures (seminal vesicles and bladder base) [ 2 , 6 - 9 ]. Of the six, two were treated with chemotherapy only [ 6 , 9 ], one was treated with chemotherapy followed by radiotherapy [ 7 ], and three were treated with a combination of surgery and chemotherapy [ 2 , 8 , 10 ]. Of the three patients who received surgery, one was treated with radical prostatectomy, another with pelvic exenteration, and the last with TURP.…”
Section: Discussionmentioning
confidence: 99%
“…It represents 1% to 3% of all GCTs and can be classified as seminomatous, which comprises 60% of all primary EGGCT formed only by the classical seminoma, and non-seminomatous including embryonal carcinoma (EC), teratoma (mature or immature), yolk sac carcinoma (YST) and choriocarcinoma. EGGCT constituted by two or more histotypes is referred to as mixed germ cell tumor [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%